Dual path mechanism of promoting classical furniture and customer responses: From the perspective of empathy - Cai, Jiajun; Yu, Lixia (Frontiers in Psychology, 2022)
The correlation between empathy and customer responses may be a key to solve the problem of classical furniture advertising design. To explore the relationship between empathy and consumer purchasing response, this study proposes a model of dual path mechanism of empathy influencing consumer purchase intentions in classical furniture through advertising design related to furniture brand Tanjuyuan. The results not only prove the hypotheses, but also indicate that: (1) cultural empathy and empathy fusion have a more significant impact on consumers' purchase intention than practical empathy; (2) cultural empathy plays a dominant role in influencing consumers' purchase intention; (3) empathy fusion is a key mediator between cultural empathy and practical empathy in influencing consumers' purchase intention. These findings provide issues for subsequent research from various perspectives, such as enhancing the practical perceptions of consumers of classical furniture products, cultural value perceptions, and the interdisciplinary application of empathy.